Changes in Vestibular/Ocular-Motor Screen Scores in Adolescents Treated With Vestibular Therapy After Concussion. Issue 4 (October 2020) - Alsalaheen, Bara; Carender, Wendy; Grzesiak, Melissa; Munday, Cindy; Almeida, Andrea; Lorincz, Matthew; Marchetti, Gregory F.
Abstract : Purpose: To examine interrelationships among Vestibular/Ocular-Motor Screen (VOMS) items and to characterize the recovery of VOMS performance in a sample of adolescents treated with vestibular physical therapy (VPT) after concussion. Methods: Seventy-seven patients with concussion and 77 participants without concussion completed the study. Adolescents with concussion received an individualized VPT intervention consisting of targeted exercises for gaze stability, postural stability, ocular-motor control, habituation, and aerobic activities. The exercises were performed during a weekly clinic visit and via a home exercise program. Results: Except for near-point convergence distance, all VOMS items were significantly interrelated. Over the course of VPT, significant improvements in VOMS performance were observed, and discharge scores were similar to scores observed in adolescents without concussion. Conclusions: The VOMS measured moderately related functions and captured changes over the course of VPT. Clinicians should consider the contextual risk of "false positive" in their interpretation of VOMS. Abstract : This study examines interrelationships between various Vestibular/Ocular-Motor Screen items, to characterize recovery in performance in a sample of adolescents after concussion.